2020
DOI: 10.2147/dddt.s278414
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cytotoxic and Antiproliferative Effects of β-Mangostin on Rat C6 Glioma Cells Depend on Oxidative Stress Induction via PI3K/AKT/mTOR Pathway Inhibition</p>

Abstract: Background: Glioma is the most common malignant tumor of the nervous system, which accounts for more than 45% of central nervous system tumors and seriously threatens our health. Because of high mortality rate, limitations, and many complications of traditional treatment methods, new treatment methods are urgently needed. β-Mangostin is a natural compound derived from the fruit of Garcinia mangostana L. and it has anticancer activity in several types of cancer cells. However, the antitumor effect of β-mangosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
0
8
1
Order By: Relevance
“…Previous studies have demonstrated that the PI3K/AKT pathway played a key role in modulating cell proliferation and apoptosis [14,15]. In glioma studies, multiple evidences revealed that the activation of PI3K/AKT pathway could enhance cell proliferation in a mTOR dependent or independent way [16][17][18]. However, as far as we could reach, no convincing evidence showed the regulatory effect of CPNE3 on PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have demonstrated that the PI3K/AKT pathway played a key role in modulating cell proliferation and apoptosis [14,15]. In glioma studies, multiple evidences revealed that the activation of PI3K/AKT pathway could enhance cell proliferation in a mTOR dependent or independent way [16][17][18]. However, as far as we could reach, no convincing evidence showed the regulatory effect of CPNE3 on PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have demonstrated that the PI3K/AKT pathway played a key role in modulating cell proliferation and apoptosis [14,15]. In glioma studies, multiple evidences revealed that the activation of PI3K/AKT pathway could enhance cell proliferation in a mTOR dependent or independent way [16][17][18]. In primary breast tumors, high CPNE3 RNA levers significantly correlate with ERBB2 amplification [10].…”
Section: Discussionmentioning
confidence: 99%
“… 46 Our previous studies have shown that the apoptosis of glioma cells by β-mangostin treatment is accompanied by BAX mitochondrial distribution, oligomerization, and caspase 3 activation. 31 Physical and chemical properties of β-mangostin can be effectively improved by encapsulation into NPs. CCK8 assay showed that β-PCNPs significantly inhibited the proliferation of C6 glioma cells as compared with that by both bare core NPs and single cell membrane-coated NPs.…”
Section: Discussionmentioning
confidence: 99%
“…30 Our previous study showed that β-mangostin, the major component of Garcinia mangostana L. extract, has excellent anti-proliferative effects in C6 glioma cells, which result from oxidative damage-induced cell death through PI3K/AKT/mTOR pathway inhibition. 31 However, aqueous solubility, tumor selectivity or targeting, and BBB penetration rate of β-mangostin does not meet clinical requirements.…”
Section: Introductionmentioning
confidence: 99%